"I'm Very Hurt": (Un)justly Reading the Black Female Body as Text in a Racial Literacy Learning Assemblage. Issue 2 (9th August 2021) - Ohito, Esther O.
ABSTRACT: There has been a recent rise in research that has attuned to matters of the body in literacy learning. This article is a contribution to that emerging corpus of scholarship. Specifically, the article is a Black feminist narrative inquiry into the undertheorized role of embodiment―and relatedly, the embodied knowing that materializes as emotion or affect―in racial literacy learning. To illustrate, I employed a blend of embodiment, affect, and assemblage theories to examine an episode of a university‐based (self‐described) anti‐racist pedagogue's racial literacy instruction in an English teacher education program in the United States. A sociomaterial approach to literacy frames my exploration of the relation between the emotions generated during classroom discourse about the contents of a curricular text used by the Black female pedagogue and the reproduction of anti‐racist ideology. Findings underscore that racial literacy instruction is (inter)embodied and affective and that each body is a particular racialized, sexed, gendered, and otherwise marked text. These findings underpin my clarion call for a turn to Black feminist racial literacy instruction, an approach entailing the enactment of reparative and healing pedagogical practices that care‐fully tend to the embodied and psychic wellness of Black women and girls in particular while simultaneously cultivating pedagogues' and students' commitments to justice and humanization in English teacher education classrooms.